2017
DOI: 10.3892/mmr.2017.8003
|View full text |Cite
|
Sign up to set email alerts
|

High‑cholesterol diet results in elevated amyloid‑β and oxysterols in rats

Abstract: The aim of the present study was to investigate the effects of diet cholesterol on oxysterol levels and amyloid‑β (Aβ) production in the peripheral blood and the brains of Sprague‑Dawley (SD) rats. SD rats were randomly divided into five groups and fed 0.015, 0.05, 0.2, 0.5 and 1.6% cholesterol‑containing diets for 8 weeks. The effect of the different diets on the levels of cholesterol, oxysterols [including 27‑hydroxycholesterol (OHC), 24S‑OHC, 7α‑OHC and 7β‑OHC], and the Aβ1‑40 and Aβ1‑42 peptides were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
6
13
0
Order By: Relevance
“…In addition, the apolipoprotein E (ApoE) knock-out mice were treated with a high-fat diet and injected intracerebroventricularly with Aβ 25–35 , the results showed that hypercholesterolemia accelerated Aβ accumulation and tau pathology, which subsequently deteriorated cognitive impairment ( Park et al, 2013 ). Similar results were obtained in several different strains of mice and Sprague-Dawley rats, with diet-induced hypercholesterolemia accelerating Aβ accumulation in the brain ( Shie et al, 2002 ; Li et al, 2003 ; Umeda et al, 2012 ; Liu et al, 2018 ). Various animal studies suggest that hypercholesterolemia increases Aβ by affecting APP processing in vivo ( Refolo et al, 2000 ; Ullrich et al, 2010 ).…”
Section: Correlation Of Hypercholesterolemia With Alzheimer’s Disease...supporting
confidence: 82%
“…In addition, the apolipoprotein E (ApoE) knock-out mice were treated with a high-fat diet and injected intracerebroventricularly with Aβ 25–35 , the results showed that hypercholesterolemia accelerated Aβ accumulation and tau pathology, which subsequently deteriorated cognitive impairment ( Park et al, 2013 ). Similar results were obtained in several different strains of mice and Sprague-Dawley rats, with diet-induced hypercholesterolemia accelerating Aβ accumulation in the brain ( Shie et al, 2002 ; Li et al, 2003 ; Umeda et al, 2012 ; Liu et al, 2018 ). Various animal studies suggest that hypercholesterolemia increases Aβ by affecting APP processing in vivo ( Refolo et al, 2000 ; Ullrich et al, 2010 ).…”
Section: Correlation Of Hypercholesterolemia With Alzheimer’s Disease...supporting
confidence: 82%
“…In this case, production, transport and elimination of Aβ may play key roles in Aβ pathology of MCI patients. While several studies including ours have manifested that the accumulation of Aβ in brain may be associated with the disturbance of 27‐OHC in brain and/or circulation , the underling mechanisms in the correlation between oxysterols and Aβ are still unclear. The second aim of this study is to investigate the molecular mechanism of excessive oxysterols on regulating Aβ metabolism.…”
Section: Introductionmentioning
confidence: 86%
“…Increased levels of 27-hydroxycholesterol (27-OHCE) were observed in the brain of AD patients [31] due to hypercholesterolemia, increased BBB permeability and reduced neuronal metabolism of 27-OHCE by oxysterol 7 a-hydroxylase, a cytochrome p450 enzyme responsible for the first and rate limiting step in bile acid synthesis [32]. Abnormal levels of oxysterols in the brain can increase Ab production [33] and worsen neuroinflammation [34]. In detail, oxysterols are endogenous activators of LXRs, which in turn play a role in the regulation of Ab in the brain by mechanisms involving cholesterol transporters [35].…”
Section: Introductionmentioning
confidence: 99%